Anatomy and Histochemistry of the Vegetative System of Brachystele guayanensis (Lindl.) Schltr. (Orchidaceae), a Potential Medicinal Species - Santos, Igor Soares dos [UNESP]; Silva, Marcos José da (MDPI, 2023)
The orchid genus Brachystele Schltr. (Orchidoideae, Cranichideae, Spiranthinae) comprises 20 species distributed from Mexico to Argentina, with 10 species found in Brazil. Anatomical studies of Orchidoideae Lindl. have been scarce, and the anatomy and histochemistry of Brachystele are still largely unknown. In this study, we conducted a characterization of the vegetative organs of B. guayanensis (Lindl.) Schltr. using standard anatomical and histochemical microtechniques. In this study, we provide the first information about the anatomy and histochemistry of Brachystele. The studied species was observed to display anatomical characters commonly found in the vegetative organs of representatives of the Cranichideae tribe (e.g., uniseriate epidermis; homogeneous mesophyll with 6–11 layers; rhizomes with rings of fibers; vascular bundles in the form of “^” or “v”; fleshy roots with uniseriate velamen, simple trichomes, and spiranthosomes). Others can be interpreted as adaptive strategies conditioned by the environment and their terrestrial life form (e.g., cuticle thickness; amphistomatic leaves; roots with reduced velamen compared to the cortex (18–20 layers); and raphides). In this study, cataphylls, and the presence of spiranthosomes in leaves, including stomatal guard cells, as well as alkaloids in these structures, are anatomically described for the first time in Orchidaceae. The presence of hyphae and pelotons in the stem of B. guayanensis is described for the first time in Cranichideae. Histochemical tests confirmed the presence of lignin, proteins, and alkaloids, the lipidic nature of the cuticle, starch grains stored in spiranthosomes, and the composition of the raphides. Alkaloids were observed in abundance, particularly in the roots, suggesting a potential role in defense against pathogens and herbivores, as well as potential medicinal activities, as seen in phylogenetically related groups to Brachystele.
Keywords: alkaloids; ergastic substances; leaf; micromorphology; orchids; rhizomes; roots